2017
DOI: 10.1038/s41598-017-16124-8
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of myeloid differentiation primary response protein 88 provides neuroprotection in early brain injury following experimental subarachnoid hemorrhage

Abstract: Accumulating of evidence suggests that activation of nuclear factor-kappa B (NF-κB) and mitogen-activated protein kinases (MAPKs) exacerbates early brain injury (EBI) following subarachnoid hemorrhage (SAH) by provoking pro-inflammatory and pro-apoptotic signaling. Myeloid differentiation primary response protein 88 (MyD88) is an endogenous adaptor protein in the toll-like receptors (TLRs) and interleukin (IL) -1β family signaling pathways and acts as a bottle neck in the NF-κB and MAPK pathways. Here, we used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 45 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…Given that microglia are phagocytic cells fulfilling their task as edaphic macrophages, the TLR4 pathway is essential for the immune response mediated by microglia [ 15 , 16 , 48 50 ]. Various components of this pathway have already been investigated in anti-inflammatory approaches regarding SAH; antagonizing inflammatory cytokines, especially IL1β or inhibition of the adapter protein MyD88 [ 51 ]. Our current results in accordance with these previous results support the significance of the TLR4 pathway in cerebral spreading inflammation after SAH.…”
Section: Discussionmentioning
confidence: 99%
“…Given that microglia are phagocytic cells fulfilling their task as edaphic macrophages, the TLR4 pathway is essential for the immune response mediated by microglia [ 15 , 16 , 48 50 ]. Various components of this pathway have already been investigated in anti-inflammatory approaches regarding SAH; antagonizing inflammatory cytokines, especially IL1β or inhibition of the adapter protein MyD88 [ 51 ]. Our current results in accordance with these previous results support the significance of the TLR4 pathway in cerebral spreading inflammation after SAH.…”
Section: Discussionmentioning
confidence: 99%
“…Siglec-10 can also inhibit the function of NK cells and T cells and to interact with HSP70, HSP90, VAP-1 to reduce in ammation [15,20]. There are many consistent contents in the research area of aSAH, such as MyD88 / NF-κB Pathway, HMGB1 and DAMPs [30][31][32][33]. Our results showed that Siglec-10 rose to peak rapidly after aSAH and remained at a high concentration afterward, indicating that Siglec-10 did participate in the pathophysiological process after aSAH, and the possible mechanisms might be the ones mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Nissl staining was performed as referred to our previous publication (Yan et al, 2017). Sections were stained with 1% toluidine blue at 50 • C for 20 min and then rinsed with doubledistilled water.…”
Section: Nissl Stainingmentioning
confidence: 99%